Evaluation of head and neck cancer patients' knowledge regarding complications of chemotherapy and radiotherapy in patients referring to Kerman University of Medical Sciences treatment centers - Molook Torabi Parizi; Mahsa Kalantari; Farshad Ghavidel (Tehran University of Medical Sciences, 2018)
Background and Aims: Cancer is the 3rd cause of death after heart disease and injuries in Iran. Radiotherapy and chemotherapy are the most effective procedures in cancer therapy, but their side effects are still unknown for many patients. The main goal of this study was to evaluate the patients’ knowledge with head and neck cancer regarding the complications of radiotherapy and chemotherapy. Materials and Methods: This descriptive-analytical research was based on the information extracted from personal questionnaires and files of cancer patients who referred to the centers of Kerman University of Medical Sciences during a 6 months period in 2017. The data were analyzed by chi-square test at the significance level of 0.05. Results: Our findings showed that most of the patients (76.48%) had low information level. There was no statistically significant association between the knowledge with demographic variables (P>0.05). However, patients with chronic disease had higher level of information. Only 10% of patients had received information by their physicians. Conclusion: It seems there is not effective education regarding the rated radiotherapy and chemotherapy complications, because their knowledge was not in acceptable level. Considering the importance of this issue, it is necessary to perform educational program to improve patients' ability and skills to cope whit the chemotherapy and radiotherapy complications and their side effects.